Pelatihan Daring Pendidikan Pancasila di Perguruan Tinggi: Habituasi Nilai-Nilai Pancasila Dalam Laku - Yayah Khisbiyah; Aris Purwanto; Paksi Hidayatulloh; Ragil Setya Budi (Abdi Psikonomi, 2020)
Pancasila values ??must be inculcated in students comprehensively, not only at the cognitive level, but also in affective domain, which impact into behavioral domain and actions. To carry out this role, students must be able to understand, appreciate and also practice the values ??of Pancasila in everyday life. However, the values ??of Pancasila as a noble culture have begun to fade among students or the millennial generation, due to intrusion of alternative values ??and culture that are not in line with Pancasila, especially in the era of globalization. This activity focuses on goals to increase understanding, appreciation, and practice of the values ??of Pancasila in real life. The form of the activity is training for trainers for students. The methods used include: the presentation of the basic values ??of Pancasila, the elaboration of the Pancasila’s concept into behavior, and reflective guidance on actualizing the values ??of Pancasila in everyday life. Through this activity, students are expected to gain additional knowledge, increase understanding and motivation to put Pancasila values ??into practice. Furthermore, students are also expected to be able to carry out self-evaluation and strive to become agents of change in spreading Pancasila values ??to their peer groups and the general public. Keywords: Students, Change Agents, Pancasila